Ecological Drivers of Non-kin Cooperation in the Hymenoptera - Ostwald, Madeleine M.; Haney, Brian R.; Fewell, Jennifer H. (Frontiers in Ecology and Evolution, 2022)
Despite the prominence of kin selection as a framework for understanding the evolution of sociality, many animal groups are comprised of unrelated individuals. These non-kin systems provide valuable models that can illuminate drivers of social evolution beyond indirect fitness benefits. Within the Hymenoptera, whose highly related eusocial groups have long been cornerstones of kin selection theory, groups may form even when indirect fitness benefits for helpers are low or absent. These non-kin groups are widespread and abundant, yet have received relatively little attention. We review the diversity and organization of non-kin sociality across the Hymenoptera, particularly among the communal bees and polygynous ants and wasps. Further, we discuss common drivers of sociality across these groups, with a particular focus on ecological factors. Ecological contexts that favor non-kin sociality include those dominated by resource scarcity or competition, climatic stressors, predation and parasitism, and/or physiological constraints associated with reproduction and resource exploitation. Finally, we situate Hymenopteran non-kin sociality within a broader biological context by extending insights from these systems across diverse taxa, especially the social vertebrates. Non-kin social groups thus provide unique demonstrations of the importance of ecological factors in mediating the evolutionary transition from solitary to group living.